Adaptasi Pola Komunikasi dari Komunitas Mahasiswa Kaum Effeminate di Yogyakarta - Septian, Rizki; Urfan, Noveri Faikar (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The phenomenon of the presence of the effeminate in Yogyakarta has begun to become a common sight. This effeminate community consists of a group of students who have similar preferences and characteristics to the nature and appearance of women. The aim of this research is to provide an overview and information regarding the communication patterns formed by members of the effeminate student community so that they can adapt in the community environment. This research uses qualitative methodology with a phenomenological approach to understand the subjective experiences and perceptions of community members. Data was collected through in-depth interviews and participant observation, then analyzed using qualitative descriptive analysis. The research results show that the effeminate community is divided into 2 levels, namely level 1 and level 2 which have gay sexuality. The process of community communication patterns is different at each level to deal with social stigma and create a safe space for themselves. Communication patterns in effeminate communities involve the use of special language and symbols. Thus, this research provides new information in the form of the composition of communication patterns adopted by the effeminate student community at each level, including their barriers to communication which are influenced by environmental and internal factors.